Acyl-CoA Dehydrogenase Deficiency and RS - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
A female infant with medium-chain acyl-CoA dehyrogenase (MCAD) deficiency who was diagnosed with Rett syndrome at 3.5 years is reported from Twenteborg Hospital, Almelo, and Wilhelmina Kinderziekenhuis, Utrecht, The Netherlands.